Analisis Konflik Antarkelas dalam Novel Si Anak Badai Karya Tere Liye - Fitri Mz Fitri Mz; Mukhlis Mukhlis; Muhammad Idham (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
The topic of this research is conflict between classes in the novel Si Anak Badai by Tere Liye. This study aims to describe the conflict between classes that occurs in the novel Tere Liye Si Anak Badai. The method used is a qualitative research method. The data source in this study is the novel Si Anak Badai by Tere Liye published by Publisher Republika in August 2019. The data in this study are words, sentences and paragraphs that contain conflicts between classes in the novel Si Anak Badai by Tere Liye. The data collection technique used in this research is documentation technique. The analysis technique used in this study is a qualitative analysis technique. The results of this study indicate that there is a conflict between classes that occurs in the novel Si Anak Badai by Tere Liye. This class conflict occurs between the upper and lower classes. The upper class was represented by Pak Alex, Camat Tiong, Utusan Gubernur, and Pak Mustar. The lower class was represented by the Captain, Wak Sidik, Wak Tukal, Paman Deham, the children of Manowa, Zaenal, and residents of Manowa village. The difference in interests between the upper and lower groups is very obvious, the upper class wants Manowa village land to be used as a port, while the lower class wants the port construction to be canceled because it is considered detrimental to the people of Manowa Village. Conflict is divided into vertical conflict and horizontal conflict. Data about horizontal conflicts or conflicts that occur between degrees such as between ethnic groups or religions are not shown because this study focuses on research between classes that are included in vertical conflict